Alloying at the nanoscale - Cai Lu; Bozhao Wu; Yangyang Pan; Hui Fang; Jianxin Liu; Xiaoqi Yang; Ze Liu (Materials & Design)
We report a general flash arc synthesis (FAS) method to batch fabricate alloy micro/nanocrystals of up to eight components on a wafer-scale. Combined with experiments and first-principle calculations, we show that the shape and size distribution of prepared micro/nanocrystals is determined by both the adhesion energy and diffusion coefficient of metal atoms on the highly oriented pyrolytic graphite (HOPG) substrate. Moreover, we show that surface atomic steps in the HOPG substrate can induce self-assembly and anchoring of metal micro/nanocrystals. The proposed method can essentially prepare alloy micro/nanocrystals with any number of components due to the high cooling rate of micro/nanocrystals, which could lead to the quick development of new materials by directly alloying on the nanoscale and facilitate the applications of alloy micro/nanocrystals.